Frizzled-9 impairs acetylcholine receptor clustering in skeletal muscle cells - Avilés, Evelyn C.; Pinto, Cristina; Hanna, Patricia; Ojeda, Jorge; Pérez, Viviana; De Ferrari, Giancarlo V.; Zamorano, Pedro; Albistur, Miguel; Sandoval, Daniel; Henríquez, Juan P. (Frontiers in Cellular Neuroscience, 2014)
Cumulative evidence indicates that Wnt pathways play crucial and diverse roles to assemble the neuromuscular junction (NMJ), a peripheral synapse characterized by the clustering of acetylcholine receptors (AChR) on postsynaptic densities. The molecular determinants of Wnt effects at the NMJ are still to be fully elucidated. We report here that the Wnt receptor Frizzled-9 (Fzd9) is expressed in developing skeletal muscles during NMJ synaptogenesis. In cultured myotubes, gain- and loss-of-function experiments revealed that Fzd9-mediated signaling impairs the AChR-clustering activity of agrin, an organizer of postsynaptic differentiation. Overexpression of Fzd9 induced the cytosolic accumulation of β-catenin, a key regulator of Wnt signaling. Consistently, Fzd9 and β-catenin localize in the postsynaptic domain of embryonic NMJs in vivo. Our findings represent the first evidence pointing to a crucial role of a Fzd-mediated, β-catenin-dependent signaling on the assembly of the vertebrate NMJ.